Hubungan Pengetahuan, Aktivitas Fisik, Nutrisi dan Personal Hygiene terhadap Dismenorea Pada Anak Remaja di MTS Al-Hidayah Salakuray Bayongbong-Garut - Neng Siti Asih Alawiyah; Milka Anggreni Karubuy; Rindu Rindu (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the factors influencing dysmenorrhea in female adolescents at MTS Al-Hidayah, Garut, in 2024. Among 20 participants, the results show that knowledge, physical activity, and diet are significantly related to the level of discomfort from dysmenorrhea. Adolescents with better knowledge, higher physical activity, and healthier diets experienced less severe dysmenorrhea. However, personal hygiene did not show a significant impact. The study emphasizes the importance of education, promoting physical activity, and improving nutrition to alleviate dysmenorrhea in adolescents.